Court interpreting in the United Kingdom: analysis of the Ministry of Justice’s Language Service New Contract - Aurora Ruiz Mezcua; Alicia Fernández Gallego-Casilda (Futhark. Revista de Investigación y Cultura, 2021)
Court interpreting is a challenging context where languages are fundamental to ensure justice and respect for human rights. The phenomenon of public service interpreting is a relatively recent one and the UK is considered to be one of the pioneer countries in providing Community Interpretation. The main objective of this research is to analyse the diverse aspects of the contract signed by the MoJ in 2012 with a private company for the outsourcing of language services. The MoJ previously obtained such services from freelance interpreters through a different system. We study the reasons for changing the old Ministry of Justice language service contract, the transition and also the new system, from an interpreting quality perspective. Consequently, this paper concentrates on one hypothesis: that there are elements in this outsourcing contract that pose a risk to the quality of the services provided under it.